FERROVIA E TURISMO: REFLEXÕES SOBRE O PATRIMÔNIO CULTURAL FERROVIÁRIO EM IRATI (PR) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
This work seeks to reflect about the railroad as a historical and cultural heritage of the city of Irati-PR, with the objective is examine the touristic use of the railway cultural heritage on this. Therefore, it is necessary to contextualize the railroad in the historical development of the city, the recognition of railway cultural heritage by the community, and analysis the public politics for the protection of railway heritage in the city. At the end of the survey, after the theoric discussion and field research in the form of interviews with government and community, is possible to see the influence of the railroad to develop Irati. This influence is recognized by the people and the government, but there are no actions to preserve the railroad heritage. Being considered as a representative element of memory and identity of the local community, the railroad can be analyzed as a potential tourism product for the city, especially for the purpose of preservation and enhancement of heritage railways. However, before the railroad being used as a tourism product, it must be as an instrument of culture appreciation for the community to be an important benchmark of identity with the past.
Keywords: ferrovia; memória; patrimônio cultural; turismo; cultural patrimony; memory; Railroad; Tourism; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA